STUDY ON MILKABILITY TRAITS OF KANKREJ COWS - Anand, D; Trivedi, M M; Dhami , A J; Divekar , `B S; Patel , À M (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
The study was undertaken on 12 suckled Kankrej cows to investigate the effects of shift of milking, season and milker on milkability traits, viz. let down time, total milking time, milk yield/milking and milk flow rate. The overall mean let down time, total milking time, milk yield/milking and milk flow rate were 67.99 seconds, 262.67 seconds, 3.32 kg and 0.77 kg/minute, respectively. The differences between morning and evening milking were non-significant for let down time, total milking time and milk yield. However, milk flow rate showed significant (P
Keywords: Kankrej; Let down time; Total milking time; Milk flow rate; Milk yield; Correlation